Peran Resiliensi Terhadap Quarter Life Crisis Pada Dewasa Awal - Khairunnisa, Nyayu Afifah Thahira; Wulandari, Primatia Yogi (CV RIFAINSTITUT, 2023)
This study aims to determine the role of resilience to Quarter Life Crisis in young adults. Excessive feeling of helplessness, confusion, and uncertainty in facing life events are called Quarter Life (Robbins & Wilner, 2001). Resilience is known to be one of the factors that influence Quarter Life Crisis. This study is a quantitative research using survey method and purposive sampling techniques for sampling to 107 young adults within the range of 21—25 years old consists of 22 men and 85 women. Data analysis used a simple linear regression. This research uses two scale, Quarter Life Crisis scale by Agustin (2012) that later on be tryout by Wijaya dan Utami (2021) and resilience scale by Asad dan Hafnidar (2023). Data analysis is using the help of IBM SPSS 27 for Windows software. The results showed that there is a role of resilience towards Quarter Life Crisis in young adults. Effect size from resilience towards Quarter Life Crisis is 22,6%, while the rest (77,4%) is affected by other variables that are not studied in this research.